OPTIMALISASI pH PRODUKSI ENZIM SELULASE DARI BAKTERI ENDOFITIK Pseudomonas stutzeri LBKURCC45, Pseudomonas cepacia LBKURCC48 DAN Pseudomonas stutzeri LBKURCC59 - Ajaib Prima; Silvera Devi; Saryono ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The isolate of LBKURCC45, LBKURCC48 and LBKURCC59 are endophytic bacteria that have been isolated from the tubers of dahlia. Endophytic bacteria can get into the plant tissue through injured plant tissue or because the bacteria can produce cellulase to degrade plant cell wall that contain cellulose. Cellulase is an enzyme that can hydrolyze the β-1-4-glycosidic bond of cellulose. This study was carried out to determine the optimum pH of cellulase enzyme production (6.0; 6.5; 7.0; 7.5; and 8.0). Enzyme activity was calculated based on the amount of reducing sugar formed from Carboxymethyl cellulose (CMC) substrate hydrolyzed by cellulase enzyme with Nelson-somogyi method. The result showed that the highest activity of cellulase enzyme obtained at pH 7 at 24 hours production time. The cellulase activity of LBKURCC45, LBKURCC48, and LBKURCC59 was 0.415 ± 0.043 x 10-3 U/mL, 0.353 ± 0.069 x 10-3 U/mL, and 0.246 ± 0.050 x 10-3 U/mL, respectively.